KONSEP MENUMBUHKAN KETERAMPILAN BERBAHASA INDONESIA BAGI ANAK MELALUI METODE BERMAIN - Aniati, Aniati (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
The world of play is the world of children. Fostering Indonesian language skills for children through play methods is a way of developing language skills with the goal of conveying ideas, ideas, concepts, and feelings through reading, listening, writing and speaking. By using play methods to foster language skills for children, such as guessing pictures, word games, chain whispers, crossword puzzles, role playing, traveling, drama, intelligent meticulous, ready to carry out orders, and make cooperation. These methods are tailored to the child's ability to receive the required material. The steps taken in fostering children's language skills through play methods include: Determining the purpose and theme of play activities, determining the kinds of play activities, determining the place and play space, determining materials and play equipment, and determining the sequence of play steps. Thus, children's language skills will grow along with the growth of activities expressed in everyday life.